Criminal policy in the sphere of sentencing (comparative-legal analysis) - Якулін, Від; Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The paper considers some aspects of the sentencing in Ukraine and Slovenia. The authors analyze sentencingpolicy as a kind of the criminal policy in general. Authors conclude that in some cases the courtsprescribe too lenient penalty. The certain issue devoted to the discretionary power of the court and the principleof retroactivity of the criminal law, which sometimes allow perpetrators to escape punishment.